Platelet c-mpl expression is dysregulated in patients with essential thrombocythaemia but this is not of diagnostic value. - Harrison, C; Gale, R; Pezella, F; Mire-Sluis, A; MacHin, S; Linch, D (1999)
Essential thrombocythaemia (ET) can be difficult to discriminate from an occult case of reactive thrombocytosis (RT). Since thrombopoietin (TPO) is the primary regulator of thrombopoiesis, we have investigated whether levels of TPO and/or its receptor, c-mpl, are of value in the differential diagnosis of ET. Plasma TPO levels in patients with ET, RT and other myeloproliferative disorders (MPDs) did not differ significantly from normal controls. However, surface c-mpl expression was significantly reduced in platelets from 18 ET patients, 0-65.5% of controls (P < 0.001). Immunoblots on five of these and five additional patients were consistent with absent or reduced c-mpl protein levels. The surface c-mpl expression results were significantly different from those in eight RT patients (21. 3-95.5%, P = 0.0015), but there was considerable overlap between the two groups and a reduced level was not restricted to ET. Furthermore, c-mpl expression in ET patients was not different from eight patients with other MPDs (0-87.6%, P = 0.06), nor could it differentiate between ET patients with monoclonal and polyclonal haemopoiesis. Although a low or absent c-mpl level is suggestive of a primary rather than a secondary thrombocytosis, it is insufficiently discriminatory to be used as a diagnostic marker for ET.